2005
DOI: 10.1111/j.1368-5031.2006.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thyroxine-suppressive therapy in patients with solitary non-toxic thyroid nodules - a randomised, double-blind, placebo-controlled study

Abstract: The efficacy of thyroxine (T(4)) for solitary non-toxic thyroid nodule remains uncertain. In this study, 60 patients with solitary non-toxic thyroid nodule were divided randomly into two groups. Group I (n = 30) received thyroxine 100 microg/day for 6 months and group II (n = 30) received placebo. The volume of the thyroid nodules in 11 patients decreased more than 50% after thyroxine therapy (36.7%, responders). In these 11 patients, the mean serum thyroglobulin level decreased significantly (340 +/- 115 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…[3][4][5][6] However, the efficacy of levothyroxine is still controversial, and long-term treatment with medication may cause adverse effects such as reduction of bone density or atrial fibrillation. 3,4,17 Laser ablation and microwave ablation as thermal ablation therapy have been introduced for treatment of benign thyroid nodules in recent years. 5,18-20 Dossing et al 21 reported that the efficacy of laser ablation for predominantly solid thyroid nodules were superior to those nodules acting as controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] However, the efficacy of levothyroxine is still controversial, and long-term treatment with medication may cause adverse effects such as reduction of bone density or atrial fibrillation. 3,4,17 Laser ablation and microwave ablation as thermal ablation therapy have been introduced for treatment of benign thyroid nodules in recent years. 5,18-20 Dossing et al 21 reported that the efficacy of laser ablation for predominantly solid thyroid nodules were superior to those nodules acting as controls.…”
Section: Discussionmentioning
confidence: 99%
“…1 Most thyroid nodules are benign, but if nodular growth causes the onset of nodulerelated symptoms such as dysphagia, cosmetic problems or a malignant change, the available remedy so far has been mainly surgery. [2][3][4] The curative surgery is not only invasive but also produces pain and cosmetic defects in patients. In addition, the damage to the thyroid function associated with surgery cannot be ignored, and a long-term administration of thyroid hormone therapy is usually needed.…”
Section: Introductionmentioning
confidence: 99%
“…Most thyroid nodules are benign [2] but some nodules require treatment for cosmetic reasons, subjective symptoms or anxiety about a malignant change [3,4]. The treatment for benign thyroid nodules consists of two parts: surgery and levothyroxine medication However, both surgery and medication have drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время в литературе приводятся данные о низкой эффектив ности супрессивной терапии -27-37% узловых об разований подвергаются клинически значимому регрессу на ее фоне [47,75]. Российская ассоциация эндокринологов [11] рекомендует использовать суп рессивную терапию с ограничениями.…”
Section: лечебная тактика при муэзunclassified